Pendampingan Pengembangan Website Desa Surabaya Kecamatan Sakra Timur Kabupaten Lomb - Suhartini; Muhammad Wasil; Zainul Amri; iqbal; Galuh Indra (Jurnal Teknologi Informasi untuk Masyarakat, 2025)
This community service activity aims to develop a digital-based village website for Surabaya Village as an information medium and a platform to promote local potential. The main problem faced by the village is the limited access to information and the absence of an accessible public information system. The program was implemented in three stages: planning (data collection and identification of information needs), implementation (website development with thematic content such as village profile, governance structure, public services, and local potential), and evaluation (functional testing and technical training for village officials). The results indicate that the developed website improves information access, enhances transparency in public services, and promotes village potential to a wider audience. It also serves as a two-way communication tool between the village administration and the community. The evaluation found that village officials still require further assistance in managing the website content independently. Overall, this program demonstrates that village information digitalization can be effectively applied with local human resources and ongoing support